2009
DOI: 10.1007/s10750-009-0002-8
|View full text |Cite
|
Sign up to set email alerts
|

Foraging patterns and kleptoparasitism among three sympatric cormorants (Phalacrocorax spp.) from the Delhi region, North India

Abstract: Cormorants, described as 'foot-propelled pursuit divers', constitute an important component of aquatic food webs and exhibit unique foraging behaviour patterns, which can be properly understood through a comparative study. Since, after a foraging dive they surface to ingest the prey, the intensity of kleptoparasitic attacks on the surface can have a major impact upon the net energetic gain for each individual. Inspite of the fact that cormorants and their habitats are severely threatened in India, their foragi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…In the case of museum bird specimens and free‐ranging chickens, we measured bill, head, tarsus and total body lengths, and the measurements ranged from 1.4 to 35.3 cm. Bill length was measured (Mahendiran & Urfi, ; Nagarajan, Lea, et al., ) as the distance from the tip of the upper mandible to the beginning of skin corners near nostrils, the proximal end of the beak (Figure a,b). Head length was measured as the distance from the nostrils to the back of the head region passing over the eye plane, and total body length was measured as the distance from the crest of the head to the base of the foot (Nagarajan, Thiyagesan, Natarajan, & Kanakasabai, ; Urfi & Kalam, ) (Figure a,b) with 0.01 mm accuracy using Vernier callipers and TPSDig2 in metric units.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of museum bird specimens and free‐ranging chickens, we measured bill, head, tarsus and total body lengths, and the measurements ranged from 1.4 to 35.3 cm. Bill length was measured (Mahendiran & Urfi, ; Nagarajan, Lea, et al., ) as the distance from the tip of the upper mandible to the beginning of skin corners near nostrils, the proximal end of the beak (Figure a,b). Head length was measured as the distance from the nostrils to the back of the head region passing over the eye plane, and total body length was measured as the distance from the crest of the head to the base of the foot (Nagarajan, Thiyagesan, Natarajan, & Kanakasabai, ; Urfi & Kalam, ) (Figure a,b) with 0.01 mm accuracy using Vernier callipers and TPSDig2 in metric units.…”
Section: Methodsmentioning
confidence: 99%
“…Our experiment under field condition using free-ranging chicken (Figure 9a,b) also substantiates this. Here, it is worthy to mention that morphometric studies under field conditions have been coming up in the last few years using digital images (Foster et al, 2008;Mahendiran & Urfi, 2010;Sonnweber, Stobbe, Zavala, Slice, & Fieder, 2013). However, most of such studies were designed to quantify shape elements of model species rather than linear size dimension.…”
Section: Live Birds Under Field Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Bertelotti & Yorio 2000, Galván 2003. It can also be seen in flock-fishing Common Mergansers Mergus merganser (Källander 2006) and Great Cormorants Phalacrocorax carbo (Lekuona & Campos 2001, Mahendiran et al 2010, and one…”
Section: Introductionmentioning
confidence: 99%
“…Typically, host numbers have been reported, but the evidence for a relationship between host numbers and kleptoparasitism risk is mixed. Some studies have reported that the risk of kleptoparasitism rises with host numbers (Garrido et al , Mahendiran and Urfi ). However, other studies have reported that the numbers of hosts and kleptoparasites were poor predictors of kleptoparasitism risk (Woodall , Varpe ).…”
mentioning
confidence: 99%